2001
DOI: 10.1037/0090-5550.46.4.417
|View full text |Cite
|
Sign up to set email alerts
|

The effect of disability claimants' coping styles on judgments of pain, disability, and compensation: A vignette study.

Abstract: Because insurance adjusters' decisions about whether to grant compensation to disability claimants are often based on subjective criteria, such decisions may be susceptible to the influence of factors irrelevant to the claimant's disabling condition. Objective: To examine whether judgments about compensation claimants are affected by the claimants' way of coping with pain and by claimant sex. Participants: Two hundred undergraduate students. Study Design: Participants made judgments about vignettes describing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 23 publications
1
30
0
3
Order By: Relevance
“…For example, it would be interesting to examine whether the absence of medical evidence for the pain may function as a prime towards social cheating and whether the relation between the absence of medical evidence for the pain and lower ratings of pain [2,3,29,30] is mediated by observers' evaluation of the valence of the patient. Another example that may function as a cue for social cheating has been suggested by MacLeod and colleagues [20], who found that observers judge adaptive copers who claim compensation as less deserving compensation than patients with maladaptive coping styles. Third, behavioural measures (e.g., approach-avoidance behaviour measures) may complement our self-report measures and strengthen the validity of our results.…”
Section: Pain -Accepted Uncorrected Manuscriptmentioning
confidence: 96%
“…For example, it would be interesting to examine whether the absence of medical evidence for the pain may function as a prime towards social cheating and whether the relation between the absence of medical evidence for the pain and lower ratings of pain [2,3,29,30] is mediated by observers' evaluation of the valence of the patient. Another example that may function as a cue for social cheating has been suggested by MacLeod and colleagues [20], who found that observers judge adaptive copers who claim compensation as less deserving compensation than patients with maladaptive coping styles. Third, behavioural measures (e.g., approach-avoidance behaviour measures) may complement our self-report measures and strengthen the validity of our results.…”
Section: Pain -Accepted Uncorrected Manuscriptmentioning
confidence: 96%
“…Observer characteristics, such as age and gender, have also been shown to affect observers' decoding of pain (Hadjistavropoulos, LaChapelle, Hale, & MacLeod, 2000a;Hadjistavropoulos, McMurtry, & Craig, 1996b;MacLeod, LaChapelle, Hadjistavropoulos, & Pfeifer, 2001). In addition, as the large double headed arrow in Figure 2 illustrates, the actions of the observer could then lead to the removal or reduction of the pain stimulus but could also affect the pain experience itself.…”
Section: Animal Modelsmentioning
confidence: 99%
“…Additional research has indicated that others' responses to high catastrophizers may vary substantially; catastrophizing appears to elicit positive responses such as the provision of instrumental support MacLeod et al, 2001) at least initially, as well as negative responses such as criticizing the sufferer in pain or responding punitively (Boothby et al, 2004;Keefe et al, 2003). A persistent demanding style of high catastrophizing is likely to, over time, become a source of strain, burden, frustration and distress for caregivers (Cano, 2004).…”
Section: Pain Communication 52mentioning
confidence: 99%
“…The choice to use a sample of medical students was motivated by the preliminary nature of the study, whose generalizability may be tested in further researches. Moreover, some previous studies on similar topics recruited students as participants (e.g., undergraduate psychology students in Chibnall, 1994 andTait, 1995; first-year medical students in Chibnall et al, 1997; undergraduate students in MacLeod et al, 2001). Yet they provided an insightful basis for subsequent studies.…”
Section: Participantsmentioning
confidence: 99%
“…In particular, a vast range of studies point to the fact that there is a discrepancy between patients' self evaluations and judgments expressed by observers, often resulting in a phenomenon of "pain underestimation" (e.g., MacLeod et al, 2001;Marquié et al, 2003;Kappesser et al, 2004;Kappesser et al, 2006). This well-established tendency might bear major consequences.…”
Section: Introductionmentioning
confidence: 99%